The Feasibility of Interactive Multimedia Validation Data Results on Folk Poetry Texts Learning in MTS Nurul Amaliyah Tanjung Morawa - Nurul Silfi Dhawira; Syahnan Daulay; Khairil Ansari (BIRCU, 2019)
This study is aimed to know the feasibility of interactive multimedia validation data results on folk poetry texts learning. The development of interactive multimedia is focused on folk poetry text material. The students are expected to learn independently through interactive multimedia that has been adjusted by the developer. The research and development population is VII grade students of MTS Nurul Amaliyah Tanjung Morawa. The research was using the 4D method, which involves four stages of research: define, design, development, and disseminate. The product of this research results in the form of interactive multimedia development of folk poetry texts is Adobe Flash CS5 media. The results shows that the feasibility of the media and material scored an average of 88.8 % with the criteria of